Failure of postexposure treatment of rabies in children - Wilde, H.; Sirikawin, S.; Sabcharoen, A.; Kingnate, D.; Tantawichien, T.; Harischandra, P.A.; Chaiyabutr, N.; de Silva, D.G.H.; Fernando, L.; Liyanage, J.B.; Sitprija, V. (Oxford University Press, 1996)
Five failures of postexposure treatment of rabies in small children with multiple severe bites on the face and head are discussed. All had received rabies immune globulin and a potent tissue-culture vaccine. However, not all wounds had been infiltrated with immune globulin. Surgical closure prior to wound injection with immune globulin was performed in three cases. Another patient had wounds sutured after an intramuscular injection of immune globulin, without wound infiltration.

Five failures of postexposure treatment of rabies in small children with multiple severe bites on the face and head are discussed. All had received rabies immune globulin and a potent tissue-culture vaccine. However, not all wounds had been infiltrated with immune globulin. Surgical closure prior to wound injection with immune globulin was performed in three cases. Another patient had wounds sutured after an intramuscular injection of immune globulin, without wound infiltration.
Indexed for MEDLINE
Keywords: Rabies-therapy; Rabies Vaccines-therapeutic use; Rabies virus-immunology